The Oxford illustrated history of the Royal Navy - Hill, J. R.; Ranft, Bryan (Oxford ; New York : Oxford University Press, 1995)
This illustrated history tells the fascinating story of how the Navy was organized, how its ships were built and how the ordinary sailor lived in times of battle and of peace. The text is supported by photographs and maps.
The wall of England, to 1500 / Susan Rose -- From the king's ships to the Royal Navy 1500-1642 / David Loades -- A permanent national maritime fighting force, 1642-1689 / J.D. Davies -- The struggle with France, 1690-1815 / John B. Hattendorf -- The eighteenth-century navy as a national institution, 1690-1815 / Daniel A. Baugh -- The shield of empire, 1815-1895 / Andrew Lambert -- Wood, sail, and cannonballs to steel, steam, and shells, 1815-1895 / David K. Brown -- Endeavour, discovery, and idealism, 1760-1895 / Roger Morris -- Life and education in a technically evolving navy, 1815-1925 / John Winton -- The battleship fleet : the test of war, 1895-1919 / James Goldrick -- Retrenchment, rethinking, revival, 1919-1939 / Geoffrey Till -- A service vindicated, 1939-1946 / Eric J. Grove -- The realities of medium power, 1946 to the present / J.R. Hill -- The Royal Navy and the post-war naval revolution, 1946 to the present / Norman Friedman.
Includes bibliographical references (pages 449-465) and index.
Keywords: Great Britain. -- Royal Navy -- History; History; Naval history